2010
DOI: 10.4073/csr.2010.1
|View full text |Cite
|
Sign up to set email alerts
|

Formal System Processing of Juveniles: Effects on Delinquency

Abstract: The Campbell Collaboration was founded on the principle that systematic reviews on the effects of interventions will inform and help improve policy and services. Campbell offers editorial and methodological support to review authors throughout the process of producing a systematic review. A number of Campbell's editors, librarians, methodologists and external peer reviewers contribute. Plain language summaryInterventions to reduce homelessness and improve housing stability are effectiveThere are large numbers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
147
1
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(154 citation statements)
references
References 42 publications
4
147
1
2
Order By: Relevance
“…Coupled with evidence that transfer policies have no deterrent effects on youthful offenders (McGowen et al 2007), 21 the weight of the evidence suggests that involvement with the juvenile justice system does more harm than good, with negative effects magnified as punishments become harsher (Petrosino, Turpin-Petrosino, and Guckenburg 2010;Mears et al 2011). This does not imply that the system cannot be effective, especially if meaningful services are provided to the youths, but that current justice system practices do not appear to deter criminal activity.…”
Section: B Effects Of Juvenile Placement and Punishment On Adolescenmentioning
confidence: 99%
“…Coupled with evidence that transfer policies have no deterrent effects on youthful offenders (McGowen et al 2007), 21 the weight of the evidence suggests that involvement with the juvenile justice system does more harm than good, with negative effects magnified as punishments become harsher (Petrosino, Turpin-Petrosino, and Guckenburg 2010;Mears et al 2011). This does not imply that the system cannot be effective, especially if meaningful services are provided to the youths, but that current justice system practices do not appear to deter criminal activity.…”
Section: B Effects Of Juvenile Placement and Punishment On Adolescenmentioning
confidence: 99%
“…Considering 29 studies of juvenile offending over 35 years Petronsino et al (2010) concluded that formal processing increased the likelihood, frequency and severity of further offending. This was true when formal processing Diversion from the formal system is part of a range of 'systems management' techniques, which inform decision-making within and beyond the YJS in order to improve outcomes for children (Haines and Case 2015).…”
Section: Promoting Diversion and Systems Managementmentioning
confidence: 99%
“…Some studies have reported promising reductions in juvenile recidivism following restorative justice interventions (Petrosino, Guckenburg, & Turpin-Petrosino, 2010), but other scholars have been more critical of these studies due to potentially biasing flaws in research design (Weatherburn, McGrath, & Bartels, 2012). Admittedly, restorative justice programs are unlikely to replace conventional justice programs in the foreseeable future.…”
Section: Restorativeness Procedural Justice and Defiance As Long-tementioning
confidence: 99%